DOI: 10.1007/978-3-540-78640-5_87
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Focal Cortical Dysplasia Lesions in MRI Using Textural Features

Abstract: Abstract. Focal cortical dysplasia (FCD) is a frequent cause of medically refractory partial epilepsy. The visual identification of FCD lesions on magnetic resonance images (MRI) is a challenging task in standard radiological analysis. Quantitative image analysis which tries to assist in the diagnosis of FCD lesions is an active field of research. In this work we investigate the potential of different texture features, in order to explore to what extent they are suitable for detecting lesional tissue. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…For example, voxels not satisfying the criteria of GMM normal tissue models derived from the Expectation Maximization (EM) algorithm (22) are detected as lesions. MRI based automated lesion detection in other neurological diseases, such as multiple sclerosis (15, 23–25), focal cortical dysplasias (26, 27) and ischemic stroke (11) has generated great interest. There are no studies that have examined the use of automated detection of neonatal ischemic injury (the focus of this work).…”
mentioning
confidence: 99%
“…For example, voxels not satisfying the criteria of GMM normal tissue models derived from the Expectation Maximization (EM) algorithm (22) are detected as lesions. MRI based automated lesion detection in other neurological diseases, such as multiple sclerosis (15, 23–25), focal cortical dysplasias (26, 27) and ischemic stroke (11) has generated great interest. There are no studies that have examined the use of automated detection of neonatal ischemic injury (the focus of this work).…”
mentioning
confidence: 99%
“…Some computational methods have been developed for other diseases such as multiple sclerosis (MS) [ 19,20 ] , focal cortical dysplasias (FCD) [ 21,22 ] , and white matter lesions (WML) [ 23 ] . Since these methods use MRI signal contrast to detect abnormalities, they can be modifi ed or extended to evaluate lesion characteristics seen with ischemia or stroke [ 23,24 ] .…”
Section: Current Computational Approaches For Lesion Detectionmentioning
confidence: 99%
“…First, computationally intensive mathematical models are generally used that hinder rapid estimation of the size and nature of the lesion which is time sensitive when used clinically [ 19,21,25,30,39 ] . Second, many current methods use anatomical brain atlases and a priori probabilistic tissue models [ 23 ] to facilitate lesion detection and reject outliers [ 19,33 ] .…”
Section: Recently Emerging Approaches For Automated Lesion Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the determination of structural and volumetric asymmetries in the human brain from MRI provides critical data for the diagnosis of abnormality [2]. Christian Loyek et al carried out the work in epilepsy prediction and developed a model for predicting focal cortical dysplasia lesions, which is a frequent cause of medically refractory partial epilepsy, in MRI using support vector machine [3]. M.C.Clarke et al developed a method for abnormal MRI volume identification with slice segmentation using Fuzzy C-means algorithm [4].…”
Section: Introductionmentioning
confidence: 99%